Nanostructures constituted by unusually small silica nanoparticles modified with metal oxides as support for ultra-small gold nanoparticles; Colloids and Surfaces A: Physicochemical and Engineering Aspects; Vol. 487 - Martynyuk O. A. Oksana Anatolievna; Kotolevich Yu. S.; Pestryakov A. N. Aleksey Nikolaevich; Mota-Morales J. D. Josue; Bogdanchikova N. E. Nina Evgenjevna (2015, 2015)
Title screen